Our experience with Russian voice prostheses long used in patents after laryngectomy with tracheoesophageal shunting and endoprosthesis replacement - L. G. Kozhanov; A. I. Kryukov; A. L. Kozhanov (Опухоли головы и шеи, 2015)
Despite broad current diagnostic capabilities, most (60–70 %) patients with larynx cancer seek medical advice only when they have stages III and IV. Until the present time, laryngectomy has remained the most common treatment option for cancer of the larynx and laryngopharynx. Tracheoesophageal shunting with endoprosthesis replacement is one of the most important surgical vocal rehabilitation techniques after laryngectomy. According to different authors» data, the mean lifetime of voice prostheses is 6–12 months. The long-term use of voice prostheses in patients after laryngectomy with tracheoesophageal shunting with endoprosthesis replacement was the object of our investigation.Patient G., aged 34 years was admitted to the Department of Head and Neck Tumors, Oncology Clinical Dispensary (OCD) One, Moscow Healthcare Department, with a diagnosis of larynx cancer spreading to lymph nodes (LN) (T3N1M0) in the left neck on September 16, 2010. Surgery involving laryngectomy with tracheoesophageal shunting and implantation of a Russian voice prosthesis, as well as radical fascial excision of LN and fat in the neck on the left side were performed on September 21, 2010. During the 4-year use of the voice prosthesis, his voice was sonorous and good. The voice prosthesis was removed in November 2014. Antifungal therapy was used; a new voice prosthesis was implanted. His speech was fluent and his voice was sonorous and good.Patient M., aged 54 years was admitted to the Department of Head and Neck Tumors, OCD One, Moscow Healthcare Department, with a clinical diagnosis of laryngopharynx cancer (T4N1M0) and an aftereffect of gamma-therapy with a summary focal dose of 42 Gy on November 18, 2003. Surgery involving laryngectomy with laryngopharyngeal resection, tracheoesophageal shunting, and endoprosthesis replacement with implantation of a Russian voice prosthesis, as well as radical fascial excision of LN and fat in the neck on the right side were performed on November 25, 2003. The voce prosthesis was removed in December 2014. Antifungal therapy was performed. A new Russian prosthesis was implanted in the tracheoesophageal shunt. His voice was sonorous and good.